1996
DOI: 10.1002/(sici)1096-9896(199604)178:4<415::aid-path548>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

p53 GENE ALTERATIONS AND p53 PROTEIN IN ORAL EPITHELIAL DYSPLASIA AND SQUAMOUS CELL CARCINOMA

Abstract: To examine the expression of p53 protein and gene alterations in oral epithelial lesions including epithelial dysplasias and primary squamous cell carcinomas, immunohistochemical and temperature gradient gel electrophoresis (TGGE) methods were applied to formalin-fixed and paraffin-embedded tissues. Morphologically normal mucosal epithelium stained negatively for p53 protein. Three out of 11 (27.3 per cent) epithelial dysplasias and 19 out of 57 (33.3 per cent) primary squamous cell carcinomas stained positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…In contrast, in 14 displastic lesions, 36% was positive for p53 mutation (Figure 2). Although relatively few studies have been made as to p53 mutations in oral premalignant lesions, 15.4% (Lazarus et al, 1995) or 27% (Kusama et al, 1996) of epithelial dysplasia has been reported to be positive for p53 mutation. Since it has been shown that the malignant potential of leukoplakia is as high as 23 ± 38% (Silverman et al, 1984), mutations of the p53 gene may be indicative of the potential of these lesions to develop into SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in 14 displastic lesions, 36% was positive for p53 mutation (Figure 2). Although relatively few studies have been made as to p53 mutations in oral premalignant lesions, 15.4% (Lazarus et al, 1995) or 27% (Kusama et al, 1996) of epithelial dysplasia has been reported to be positive for p53 mutation. Since it has been shown that the malignant potential of leukoplakia is as high as 23 ± 38% (Silverman et al, 1984), mutations of the p53 gene may be indicative of the potential of these lesions to develop into SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of p53 mutations has been studied best in colorectal adenocarcinoma where mutations of p53 gene most frequently occur between the stages of late adenoma and invasive carcinoma (Fearon and Vogelstein, 1990). Mutations of p53 have also been observed in a variety of non-invasive, dysplastic epithelial lesions from various tissues, including oral cavity (Lazarus et al, 1995;Kusama et al, 1996), esophagus (Casson et al, 1991;Bennett et al, 1992), and lung (Sozzi et al, 1992). These data suggest that mutations of p53 gene may be an early event in squamous epithelium during progression to cancer.…”
Section: Introductionmentioning
confidence: 96%
“…Alteration of the p53 gene is known to be detectable in 50% of squamous cell carcinomas of the head and neck (21,22). No reaction for p53 protein was observed in this case, suggesting that the possibility of carcinogenesis was low.…”
Section: Discussionmentioning
confidence: 59%
“…It is an invasive epithelial neoplasm of the oral cavity showing various degrees of squamous differentiation, and a propensity for early and extensive lymph node metastasis (17). Kusama et al have previously demonstrated p53 mutation in OSCC, suggesting that this mutation is involved in the early stages of the dysplasia-carcinoma sequence in the oral squamous epithelium (18). Moreover, recent studies have suggested an association between periodontal disease and the risk of various human malignant neoplasms, including poorly differentiated OSCC (19,20).…”
Section: Introductionmentioning
confidence: 98%